Repeat Enhanced Wake up Call Endophthalmitis - Chaudhry, M. Lateef (Pakistan Journal of Ophthalmology, 2009)
Post operative endophthalmitis is a grave complication with disastrous consequences refer to a review article on this important topic by Khawaja Khalid Shoaib page 111 of present issue and an unusual case report of endogenous endophthalmitis by Mustafa Iqbal etc at page 116 also present issue of PJO by Prof. M Lateef Chaudhry Editor-in-Chief.